Jawwad Ridla's Interpretation of Islamic Educational Philosophical Schools - Mupti Al Umam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
. Islamic education is a process that takes place continuously and sustainably. Based on this, the tasks and functions that Islamic education needs to carry out are education for the whole person and lasts throughout life. This concept means that the tasks and functions of education are targeted at students who continue to grow and develop dynamically from the womb until the end of their lives. The objectives of this research are 1) what is Islamic education? 2) What are the schools of Islamic education that demand jawwad ridha? The research method in this article uses literature research through document analysis in the form of literature study. The form of this research is qualitative with a descriptive method in the form of a depiction of a particular situation or phenomenon using interactive methods. There are three schools of thought proposed by Jwaad Ridha, namely conservative religious, rational religious and pragmatic. There are several aspects to the Islamic Education Theory built by Muhammad Jawwad Ridla, including the Concept of Teaching/Learning, Psychological Basics of the Learning Process, Understanding of Educational Subjects, Teaching Methods, Teaching (Teachers) and Preparation of Individuals to Actively Participate in the Economic Life of Society. Muhammad Jawwad Ridla classifies three main schools of Islamic educational philosophy with the main figures in each of these schools. The three main schools of Islamic educational philosophy that have been discussed above have different opinions from one another.